"Two Truths and a Lie" as a Class-Participation Activity. Issue 1 (2nd January 2023) - Gelman, Andrew
Abstract: We adapt the social game "Two truths and a lie" to a classroom setting to give an activity that introduces principles of statistical measurement, uncertainty, prediction, and calibration, while giving students an opportunity to meet each other. We discuss how this activity can be used in a range of different statistics courses.